Media Pembelajaran Kampung Raja Prailiu Kabupaten Sumba Timur Berbasis Augmented Reality - Duka, Alsha Day; Malahina, Edwin Ariesto Umbu (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
The rapid development of digital technology has a significant impact in various fields, including cultural preservation. Augmented Reality (AR) is a technology that combines two-dimensional or three-dimensional virtual objects into the real world and then projects them in real time, making learning about culture more interactive and interesting. Effect House is a platform that allows the development of interactive AR effects, including Head tracking features, which can be integrated with social media such as TikTok. Therefore, the purpose of this research is to develop AR-based interactive learning media with Head tracking quiz features as a solution in learning and preserving the culture of Kampung Raja Prailiu in East Sumba Regency. This village has cultural wealth such as traditions, traditional houses, ikat weaving, and typical traditional rituals that must be introduced, preserved and passed on to the younger generation. Through the Head tracking quiz features, users can learn about the culture of Raja Prailiu Village by moving their head to select answers in an interactive quiz. At the end of the quiz, users will get a total score as an evaluation of their understanding of the culture of Kampung Raja Prailiu. With this research, the learning proces become more interesting and interactive.